Unilateral or bilateral V-Y fasciocutaneous flaps for the coverage of soft tissue defects following total knee arthroplasty - Papaioannou, Konstantinos (BioMed Central, 2010)
BACKGROUND: Soft tissue necrosis following total knee arthroplasty (TKA) may be the cause of the devastating complication of deep infection. It necessitates an immediate operative intervention because it could potentially jeopardise the arthroplasty or even the limb. METHODS: Sixteen consecutive patients with a mean age of 73,8 years (range 47 to76 years) over a 6-year period (January 2003 to December 2008) with wound dehiscence after TKA were enrolled in the present study. Unilateral or bilateral fasciocutaneous V-Y flaps that are differently oriented, depending on the local conditions of the tissues were used to reconstruct the soft tissues defects. RESULTS: In 15 of the 16 cases studied, the wound was successfully covered with the presented technique while in 1 patient a partial flap loss occurred, which was healed after surgical debridement and the application of vacuum system. No other complications occurred. Knee prosthesis was salvaged in all the patients with a good functional and esthetical outcome. CONCLUSIONS: The presented reconstructive technique is a simple, quick, versatile and reliable solution for the coverage of soft tissue defects following TKA, more than 2 cm width and grade 1 and 2 according to Laing classification, provided the V-Y flaps are applied early in the postoperative period and no complex defects are involved.